1, 1, 2, 2‐Tetrachloroethane (TeCA) as a Solvent Additive for Organic Hole Transport Materials and Its Application in Highly Efficient Solid‐State Dye‐Sensitized Solar Cells. Issue 10 (26th February 2015) - Xu, Bo; Gabrielsson, Erik; Safdari, Majid; Cheng, Ming; Hua, Yong; Tian, Haining; Gardner, James M.; Kloo, Lars; Sun, Licheng
<x xml:space="preserve">Abstract</x> A low‐cost, chlorinated hydrocarbon solvent, 1, 1, 2, 2‐tetrachloroethane (TeCA), is used as an effective additive for the triarylamine‐based organic hole‐transport material, Spiro‐OMeTAD, which is successfully applied in highly efficient solid‐state dye‐sensitized solar cells. A record power conversion efficiency of 7.7% is obtained by using the donor (D)‐π‐acceptor (A)‐dye, LEG4, in combination with the new method of TeCA‐doping of the hole‐transporting material Spiro‐OMeTAD.